Musculoskeletal health in elite male adolescent middle-distance runners - Greene, D. A.; Naughton, G. A.; Briody, J. N.; Kemp, A.; Woodhead, H.; Farpour-Lambert, N. (Journal of Science and Medicine in Sport, 2004)
The impact of high training volumes on musculoskeletal adaptations of male adolescents is poorly understood. We compared bone mineral content (BMC) of total body, lumbar spine and proximal femur using Dual X-ray Absorptiometry (Lunar Prodigy, GE Medical Systems, Madison WI) in elite level (n=20), male adolescent middle distance runners (mean 16.8 yrs, range 14-18 yrs) and age-matched (n=20) controls. Athletes averaged 14 hrs of physical activity per week and controls reported participating in physical activity an average of two hrs per week. Total body mass was 10.97 kg less in athletes than controls (p=0.005). Within the total body mass difference, fat tissue mass of athletes was 10.93 kg less in athletes than controls (p= 0.001). Multiple regression analysis identified total body lean mass and total body fat mass as the strongest predictors of total body BMC (R2 0.71). After adjusting for lean tissue mass per kg of body weight (p=0.07), no difference in BMC was detected. Lower limb muscle strength and macronutrient intakes were also measured but no between group differences were found. The number of weeks of training and/or competition missed through injury was not associated with total body BMC (R2=0.19) among athletes. Our results imply high training volumes in middle distance running are not detrimental to musculoskeletal health and are associated with positive body composition profiles in elite adolescent male athletes.